31 Ambitions for palliative and end of life care: mapping examples of use in practice. (30th January 2023) - Borgstrom, Erica; Henry, Claire; Jordan, Joanne; St-Ledger, Una
Abstract : Introduction: The Ambitions for Palliative and End of Life Care: a national framework for local action (2015) was relaunched in 2021 for another five years. The Framework focuses on six ambitions, underpinned by eight guidance for action foundations. To date, there has been no research to understand how the framework has been used in a range of settings. Aims: To explore where, how and why people have used the Ambitions Framework. Methods: Solicited responses of examples of use of the Ambitions Framework using an online survey (open and closed questions; Nov 2021-Jan 2022). We mapped responses across geographical and service areas and identified case studies for each Ambition. Results: Services use the Framework across England. The majority of examples came from hospice and/or specialist palliative care settings. Each person is seen as an individual (Ambition 1) was most frequently identified as a primary focus. Each community is prepared to help (Ambition 6) was least frequently identified as a primary focus. The Framework is most frequently being used to provide guiding principles and to support education and training. Survey respondents identified the Framework as having a role in enabling a process of service development from strategic conception to practical delivery, although there are persistent concerns about how ambitions can be meaningfully operationalised, measured, and resourced. Conclusions: Overall, the Framework appears to be well received by survey respondents. It is perceived to provide a shared language about what matters in palliative and end of life care. Impact: There is appetite for further education and knowledge exchange about the Framework and how people have used it. Ongoing research is investigating areas of implementation and notions of community. Reference: Borgstrom E, Jordan J, Henry C. (2022). Ambitions for palliative and end of life care: mapping examples of use in practice. Milton Keynes: The Open University